The research of double-pulse discharge in a plasma-liquid system with cylindrical geometry - Chernyak, V.Ya.; Sidoruk, S.M.; Yukhymenko, V.V.; Marchuk, V.E.; Martysh, E.V.; Fedorovich, O.A.; Andryuschenko, V.О. (Вопросы атомной науки и техники, 2012)
The results of acoustic signals generation by two consistent dischargers of microsecond duration in a cylindrical liquid system are presented. The radius/height ratio of the cylinder, made of stainless steel, is ~ 13.5. Both discharges occur between two electrodes located on the cylinder axis. Height of the cylinder / interelectrode distance ratio is 13.5. The delay time between the discharges has been regulated and changed in a broad spectrum: before and after the axial collapse of the cylindrical converging wave reflected from the wall. The switches were: the air discharger for the first discharge and hydrogen thyratron for the second one. Представлены результаты исследований генерации акустических сигналов двумя последовательными разрядами микросекундной длительности в цилиндрической жидкостной системе. Отношение радиуса к высоте цилиндра из нержавеющей стали составляло ~ 13,5. Оба разряда происходили между двумя електродами, расположенными на оси цилиндра. Отношение высоты цилиндра к межэлектродному расстоянию было >10. Время задержки между разрядами могло изменяться в широком диапазоне: до и после коллапса на оси сходящейся цилиндрической акустической волны, отраженной от металлической цилиндрической стенки. В качестве коммутаторов разрядов использовались воздушный разрядник для первого разряда и водородный тиратрон для второго. Представлено результати досліджень генерації акустичних сигналів двома послідовними розрядами мікросекундної тривалості в циліндричній рідинній системі. Відношення радіуса до висоти циліндра з нержавіючої сталі становило ~ 13,5. Обидва розряди відбувалися між двома електродами, розташованими на осі циліндра. Відношення висоти циліндра до міжелектродної відстані було > 10. Час затримки між розрядами міг змінюватися в широкому діапазоні: до і після колапсу на осі збіжної циліндричної акустичної хвилі, відбитої від металевої циліндричної стінки. В якості комутаторів розрядів використовувалися повітряний розрядник для першого розряду і водневий тиратрон для другого.